A Paley-Wiener Theorem for Periodic Scattering with Applications to the Korteweg-de Vries Equation - Egorova, I.; Tesch, l G. (Журнал математической физики, анализа, геометрии, 2010)
A one-dimensional SchrÄodinger operator which is a short-range perturbation of a finite-gap operator is considered. There are given the necessary and su±cient conditions on the left/right reflection coeffcient such that the difference of the potentials has finite support to the left/right, respectively. Moreover, these results are applied to show a unique continuation type result for solutions of the Korteweg{de Vries equation in this context. By virtue of the Miura transform an analogous result for the modified Korteweg-de Vries equation is also obtained.